Criticality as a signature of healthy neural systems: multi-scale experimental and computational studies - Dietmar Plenz (Frontiers Research Topics, 2015)
Since 2003, when spontaneous activity in cortical slices was first found to follow scale-free statistical distributions in size and duration, increasing experimental evidences and theoretical models have been reported in the literature supporting the emergence of evidence of scale invariance in the cortex. Although strongly debated, such results refer to many different in vitro and in vivo preparations (awake monkeys, anesthetized rats and cats, in vitro slices and dissociated cultures), suggesting that power law distributions and scale free correlations are a very general and robust feature of cortical activity that has been conserved across species as specific substrate for information storage, transmission and processing. Equally important is that the features reminiscent of scale invariance and criticality are observed at scale spanning from the level of interacting arrays of neurons all the way up to correlations across the entire brain. Thus, if we accept that the brain operates near a critical point, little is known about the causes and/or consequences of a loss of criticality and its relation with brain diseases (e.g. epilepsy). The study of how pathogenetical mechanisms are related to the critical/non-critical behavior of neuronal networks would likely provide new insights into the cellular and synaptic determinants of the emergence of critical-like dynamics and structures in neural systems. At the same time, the relation between the impaired behavior and the disruption of criticality would help clarify its role in normal brain function. The main objective of this Research Topic is to investigate the emergence/disruption of the emergent critical-like states in healthy/impaired neural systems.